COMMUNICATION TROUGH PLAY- DEVELOPER OF PRESCHOOLER’S DIALOGUE SPEECH - Stangaine, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the nowadays education is the upbringing of a cultural person striving for mutual understanding, dialogue and communication. Along with being a speech form dialogue is also manifesting various behaviours of a person. Participation in a dialogue takes place with the help of the dialogue speech, the acquisition of which is a precondition for successful development of a child and his/her activity. Significant role in the children communication is fulfilled by both linguistic content of the communication (phrases, expressions) and ability to subject linguistic forms to the social background, as at the preschool age dialogue serves for life and daily communication. Topicality of the problem lays in the fact that traditional teaching process in pre-school is organised mainly as expository monologue, insufficiently using main activity of the child – play. The results acquired within the framework of the research allow concluding that play during the communication with peers ensures speech activities, development of dialogue speech and cooperation with peers.